2011
DOI: 10.1126/science.1203285
|View full text |Cite
|
Sign up to set email alerts
|

Coupled, Circumferential Motions of the Cell Wall Synthesis Machinery and MreB Filaments in B. subtilis

Abstract: Rod-shaped bacteria elongate by the action of cell-wall synthesis complexes linked to underlying dynamic MreB filaments. To understand how the movements of these filaments relate to cell wall synthesis, we characterized the dynamics of MreB and the cell wall elongation machinery using high-precision particle tracking in Bacillus subtilis. We found that MreB and the elongation machinery moved circumferentially around the cell, perpendicular to its length, with nearby synthesis complexes and MreB filaments movin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
564
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 497 publications
(602 citation statements)
references
References 19 publications
36
564
1
1
Order By: Relevance
“…S4). Although not explored here, the MreB polymers we observe are dynamic and move circumferentially over long-time scales as reported previously (7,25,26).…”
Section: Mreb Msfgfp Is Minimally Perturbativesupporting
confidence: 73%
“…S4). Although not explored here, the MreB polymers we observe are dynamic and move circumferentially over long-time scales as reported previously (7,25,26).…”
Section: Mreb Msfgfp Is Minimally Perturbativesupporting
confidence: 73%
“…It is thus plausible that MreB filaments are physically linked to the enzymes responsible for cell-wall insertion. In fact, some of the cellwall-synthesis enzymes have been seen to move in a similar manner as MreB filaments in the Gram-positive B. subtilis (Garner et al 2011;Domínguez-Escobar et al 2011), supporting the hypothesis of physical interaction. In Gram-negative E. coli, at least one important synthesising enzyme, the transpeptidase PBP2, moves rapidly and diffusively, showing no processivity on the sub-second time scale (Lee et al 2014), thus suggesting a more transient interaction of the cell-wall synthesis proteins.…”
Section: Necessity For Regulationmentioning
confidence: 57%
“…The length of the MreB filaments is currently under debate, in particular because native-expression-level MreB filaments have not been detected in whole cells by electron microscopy (Swulius and Jensen 2012). Irrespective of their exact length, it has been shown by fluorescence microscopy that MreB filaments rotate around the long cell axis in a processive manner in Gram-negative (Teeffelen et al 2011) and Gram-positive bacteria (Garner et al 2011;Domín-guez-Escobar et al 2011;Olshausen et al 2013;Reimold et al 2013). This rotation depends on PG synthesis and proceeds at a speed compatible with processive insertion of single glycan strands into the PG meshwork (Teeffelen et al 2011), as already suggested by Burmann and Park in the 1980s (Burman and Park 1984).…”
Section: Necessity For Regulationmentioning
confidence: 99%
“…5B and C). Peaks of fluorescence, corresponding to the sites of PG insertion, were evenly distributed with an average spacing between approximately 0.5 and 1 μm, consistent with the reported spacing between the tracks followed by MreB‐associated PG synthetic machineries along the sidewalls of B. subtilis (Dominguez‐Escobar et al ., 2011; Garner et al ., 2011). …”
Section: Resultsmentioning
confidence: 99%